Sex differences in neurodegeneration and memory performance in preclinical autosomal dominant Alzheimer's disease: Baseline findings from the API ADAD trial: Intersections of sex/gender and race/ethnicity in cognitive aging and Alzheimer's disease trajectories. (7th December 2020) - Vila‐Castelar, Clara; Tariot, Pierre N; Sink, Kaycee M; Clayton, David; Langbaum, Jessica B; Thomas, Ronald G; Chen, Yinghua; Su, Yi; Hu, Nan; Giraldo‐Chica, Margarita; Tobon, Carlos; Acosta‐Baena, Natalia; et al.
Abstract: Background: Growing evidence suggests that females have greater biological risk for Alzheimer's disease (AD). As levels of AD pathology increase, females show greater tau accumulation, faster hippocampal volume loss, and faster cognitive decline than males. We sought to investigate sex differences in individuals with preclinical autosomal dominant AD (ADAD), who are destined to develop early‐onset dementia and have minimal age‐related confounds known to vary by sex (e.g., mortality, cardiovascular disease, or menopause). We plan to examine the role of sex in the associations among markers of pathology, neurodegeneration, and cognition leveraging baseline data from the Alzheimer's Prevention Initiative (API) ADAD Colombia Trial. Methods: We analyzed baseline data from 242 cognitively unimpaired 30‐53 year‐old prevention trial participants, including 167 PSEN1 E280A mutation carriers and 75 non‐carrier family members. Clinical ratings, CERAD word list delayed recall, hippocampal grey matter volume, florbetapir cortical‐to‐pontine standard‐uptake value ratios (SUVR), and precuneus 18 F‐fludeoxyglucose (FDG) positron emission tomography were included in the analyses. T‐tests and multiple regressions models controlling for age, PSEN1 mutation status and amyloid burden were conducted. Results: Across groups, females had greater hippocampal volumes (p=.05) and better delayed recall (p=.005) than males. Female carriers were younger than male carriers (p=.04). Females continued to have better delayed recall after adjusting for glucose metabolism in the precuneus (Sex: β=.562, p=.023), and showed a trend towards significance after adjusting for hippocampal volumes (Sex: β=.462, p=.059). In carriers only, as age increased, males had lower hippocampal volumes than females (Slope difference: p ≤ .05), while no differences were found in amyloid levels or metabolism. There was no sex difference in the relationship between amyloid accumulation, hippocampal volumes (Sex: β=.000, p=.094), and metabolism (Sex: β=‐.004, p=.815). Conclusion: Findings suggest that cognitively unimpaired female mutation carriers may have greater cognitive resilience to AD‐related neurodegeneration compared to male mutation carriers. Further investigation of sex‐specific differences in AD‐related clinical and pathological markers is key to inform AD detection, prevention, and development of treatments.